Harvesting Technology and the Transformation of Women's Roles in Rural Areas - Rizali, Repi; Kinseng, Rilus A.; Saharuddin (International Journal of Science and Society, 2025)
The shift from traditional to modern harvesting methods has significantly impacted the labor structure of rural farmers. Traditional harvesting technologies, which actively engaged women, contrast with modern mechanized harvesting techniques that exclude women from harvesting activities. This study aims to analyze the development of harvesting technologies in Cikeusik Village and examine the effects of modernization on women’s roles, social positions, and power relations within the agrarian structure of Cikeusik Village. A descriptive qualitative approach was employed, utilizing in-depth interviews, observations, and document analysis for data collection. The informants consisted of six female farmers, two combine harvester operators, and two community leaders, selected purposively using snowball sampling techniques. The findings reveal three distinct phases of harvesting technology in Cikeusik: traditional harvesting using ani-ani (pre-1970), the transition from ani-ani to sickles and threshing (1980–2017), and the use of combine harvesters (2017–present). The introduction of combine harvesters drastically reduced women’s participation in harvesting activities, shifting a previously female-dominated labor force to a task performed exclusively by a few male operators. Consequently, women lost a source of seasonal income and transitioned primarily into entrepreneurship or conventional domestic roles.